The cost-effectiveness of a structured education pulmonary rehabilitation programme for chronic obstructive pulmonary disease in primary care: the PRINCE cluster randomised trial. Issue 11 (25th November 2013) - Gillespie, Paddy; O'Shea, Eamon; Casey, Dympna; Murphy, Kathy; Devane, Declan; Cooney, Adeline; Mee, Lorraine; Kirwan, Collette; McCarthy, Bernard; Newell, John; ,
Abstract : Objective: To assess the cost-effectiveness of a structured education pulmonary rehabilitation programme (SEPRP) for chronic obstructive pulmonary disease (COPD) relative to usual practice in primary care. The programme consisted of group-based sessions delivered jointly by practice nurses and physiotherapists over 8 weeks. Design: Cost-effectiveness and cost-utility analysis alongside a cluster randomised controlled trial. Setting: 32 general practices in Ireland. Participants: 350 adults with COPD, 69% of whom were moderately affected. Interventions: Intervention arm (n=178) received a 2 h group-based SEPRP session per week over 8 weeks delivered jointly by a practice nurse and physiotherapist at the practice surgery or nearby venue. The control arm (n=172) received the usual practice in primary care. Main outcome measures: Incremental costs, Chronic Respiratory Questionnaire (CRQ) scores, quality-adjusted life years (QALYs) gained estimated using the generic EQ5D instrument, and expected cost-effectiveness at 22 weeks trial follow-up. Results: The intervention was associated with an increase of €944 (95% CIs 489 to 1400) in mean healthcare cost and €261 (95% CIs 226 to 296) in mean patient cost. The intervention was associated with a mean improvement of 1.11 (95% CIs 0.35 to 1.87) in CRQ Total score and 0.002 (95% CIs −0.006 to 0.011) in QALYs gained. These translated into incremental cost-effectiveness ratios of €850 per unit increase in CRQ Total score and €472 000 per additional QALY gained. The probability of the intervention being cost-effective at respective threshold values of €5000, €15 000, €25 000, €35 000 and €45 000 was 0.980, 0.992, 0.994, 0.994 and 0.994 in the CRQ Total score analysis compared to 0.000, 0.001, 0.001, 0.003 and 0.007 in the QALYs gained analysis. Conclusions: While analysis suggests that SEPRP was cost-effective if society is willing to pay at least €850 per one-point increase in disease-specific CRQ, no evidence exists when effectiveness was measured in QALYS gained. Trial Registration: Current Controlled Trials ISRCTN52 403 063.